An Overview of Lithium-Ion Battery Safety: Existing Problems and Potential Solutions - Fu Wenduo; Sun Shiqi; Wang Bo (E3S Web of Conferences)
Lithium-ion batteries (LiBs) are extensively utilised in the energy sector owing to their superior performance. In this paper, thermal runaway (TR) is introduced as one of the safety dangers, analysed the mechanism and characteristics of it. This paper focuses on the optimization of Lib, which can reduce the TR caused by mechanical, electrical and TR. The study suggests improvements in three crucial areas: electrode materials, electrolytes, and separators, aiming to reduce the dangers of TR in LiBs. Through doping, coating, nanoparticle design, and metal atom replacement, electrode materials can be improved to increase cathode safety, LiF coatings on NCM811 cathodes are one prominent example. By adding chemicals like flame retardants and creating solid-state electrolytes, electrolyte optimization greatly increases battery safety. Furthermore, improving separator stability by applying ceramic coatings, high-temperature-resistant polymers, and surface modifications fortifies mechanical and thermal endurance, lowering the risk of TR and short circuits. When combined, these methods make the LiB system safer and more dependable.